2020
DOI: 10.22225/jj.7.1.1654.65-72
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Citizenship Behavior (OCB) Towards Work Stress and Performance of Employees in Income Agency Regional City of Denpasar

Abstract: This research aims was to analyze and determine the effect of OCB on work stress and employee performance at the Denpasar City Revenue Agency. The hypothesis proposed based on theoretical studies and phenomena set forth in the formulation of the problem are 1) OCB has a positive and significant effect on employee performance, 2) OCB has a positive and significant effect on work stress, 3) Job stress has a negative and significant effect on employee performance, 4) Job stress is able to mediate OCB relations to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…The result supports the study of Kamali and Moslemipour (2016), Pratiwi and Suparta (2018), and Pranata and Yasa (2020), which revealed a positive and significant relationship between organizational citizenship behavior and the job performance of employees. Exhibiting organizational citizenship behavior in terms of altruism, civic virtue, conscientiousness, courtesy, and sportsmanship is vital to improve teachers' job performance.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The result supports the study of Kamali and Moslemipour (2016), Pratiwi and Suparta (2018), and Pranata and Yasa (2020), which revealed a positive and significant relationship between organizational citizenship behavior and the job performance of employees. Exhibiting organizational citizenship behavior in terms of altruism, civic virtue, conscientiousness, courtesy, and sportsmanship is vital to improve teachers' job performance.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, Romle et al (2016) found that five OCB dimensions positively impacted employee performance in a study of higher education institutions that emphasized the impact of the various dimensions on employee performance. According to Pratiwi and Suparta (2018) and Pranata and Yasa (2020), organizational citizenship behavior has a beneficial and statistically vital impact on employee performance, both concurrently and in part (Setiaji & Lo, 2020).…”
Section: Organizational Citizenship Behavior and Job Performancementioning
confidence: 99%
“…Pada penelitian Zaman & Tjahjahningsih (2017) hasil uji hipotesis menunjukkan bahwa modal psikologis dan OCB memiliki pengaruh positif dan signifikan terhadap kinerja karyawan, sehingga kepuasan kerja dapat memediasi modal psikologis dan OCB terhadap pembantu pembina keluarga berencana desa dalam pemberdayaan perempuan dan kinerja Keluarga Berencana. OCB berpengaruh positif dan signifikan terhadap kinerja karyawan (Pranata et al, 2020). Kemudian pada penelitian Suwibawa et al (2018) mengemukakan bahwa budaya organisasi berpengaruh positif terhadap kinerja karyawan, baik secara parsial maupun melalui OCB.…”
Section: Diskusiunclassified
“…Research related to organizational citizenship behavior has been conducted by Pranata, Sitiari, & Yasa, (2020) with the title "The Effect of Organizational Citizenship Behavior (OCB) Towards Work Stress and Performance of Employees in Income Agency Regional City of Denpasar". This study focuses on knowing the effect of organizational citizenship behavior on work stress and employee performance at the Denpasar City Revenue Service.…”
Section: A Introductionmentioning
confidence: 99%